1997
DOI: 10.1007/s002470050194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of contrast media for bronchography

Abstract: From the histologic and imaging results, barium is the best available contrast material for bronchography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…Beginning with the historic use of Barium for bronchography in 1967, which was later described as a "deadly examination," safety of contrast agents has remarkably improved. [14][15][16] Although aspiration of barium sulfate into the bronchial tree was once thought to be harmless, serious complications and several deaths have been reported due to barium aspiration in both children and adults. 8,10,11,17,18 Barium has been shown to persist in distal airspaces and has long been thought to collect in the mediastinum and cause granuloma and chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning with the historic use of Barium for bronchography in 1967, which was later described as a "deadly examination," safety of contrast agents has remarkably improved. [14][15][16] Although aspiration of barium sulfate into the bronchial tree was once thought to be harmless, serious complications and several deaths have been reported due to barium aspiration in both children and adults. 8,10,11,17,18 Barium has been shown to persist in distal airspaces and has long been thought to collect in the mediastinum and cause granuloma and chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…After iopamidol administration, the regeneration was not completed in the course of two days (Konnldova et al 1996). Recently, the light microscopic study of the rabbits' airways after iohexol tracheobronchography showed relatively severe inflammatory and even necrotic changes in the area of the mucous membrane (Thompson et al 1997). Therefore, we decided to extend our studies and to investigate also the reaction of the epithelium in terminal bronchioles to this diagnostic procedure.…”
mentioning
confidence: 99%
“…Yet according to an animal experiment (28) and previous clinical studies (10-13), a small volume of barium instillation did not show significant pulmonary parenchymal damage and is considered to be safe (10-13, 28). We believe that the very small amount of barium sulfate used in our study is does not pose that risk.…”
Section: Discussionmentioning
confidence: 99%